Practices of healthcare professionals from the perspective of older adults living with cancer - Lucimara Sonaglio Rocha; Margrid Beuter; Eliane Tatsch Neves; Juliane Elis Both; Miriam da Silveira Perrando; Larissa Venturini (Rev Rene, 2016)
Objective: understanding the care practices of health professionals caring for older adults living with cancer in outpatient treatment. Methods: a qualitative research conducted in a hematology oncology outpatient clinic in southern Brazil. A semi-structured interview was conducted with 15 older adults. Data were submitted to thematic analysis. Results: a category of care practice of health professionals amongst older adults living with cancer emerged with two subcategories: disclosure of the disease diagnosis and authoritarian educational practices. Conclusion: despite the existence of legal instruments made available to users of healthcare services, healthcare professional practices are still based on asymmetric relationships through which they place themselves as the only ones responsible for the care of the older adults, demanding adherence to their prescriptions without question, and disregarding the older adult’s care of themselves.